A the article The Effect of Voice and Accountability, Political Stability no Violence, Rule of Law on the Corruption Perception Index (CPI) - Imanuela, Aprilia Vana (International Economic Conference of Business and Accounting, 2024)
Corruption is the biggest challenge in achieving the Sustainable Development Goals (SDGs) in countries in the world. This study aims to analyze the effect of voice and accountability, political stability, and the rule of law on the corruption perception index (CPI). Using world bank and transparency international data from 168 countries during 2017-2021, the results show that Voice and accountability, Political Stability no Violence, and Rule of Law have a positive effect on CPI. These findings indicate that voice and accountability country have political stability and good law enforcement tend to have a high CPI. Therefore, a strategy to increase a country’s CPI needs to be supported by government policies to create accountability, political stability, and law enforcement, so that strategies and policies to increase this CPI can simultaneously become a strategy for achieving SDGs in a country.